Effect of fluopyram and liquid chicken manure preparation on root-knot nematodes (Meloidogyne spp.) in carrot crop - Brmež, Mirjana (Array, 2019)
The aim of this study was to investigate the nematocidal effect of the preparations based on fluopyram (pesticide) and liquid chicken manure (natural amendment) on the population density of the root-knot nematodes, Meloidogyne spp. in carrot crops. The field experiment was set up in four treatments: control (C), fluopyram (FLU), fluopyram and liquid chicken manure (FLU+LCM) and liquid chicken manure (LCM) by a random block design in four replicates. Population density of Meloidogyne spp. juveniles varied between the treatments, and the number of Meloidogyne spp. was significantly decreased in all treatments with fluopyram (FLU and FLU+LCM). All amended treatments (FLU, FLU+LCM, LCM) decreased galling of the roots and had a positive effect on carrot yield. The population of Meloidogyne spp. juveniles increased with the plant growth, regardless of the treatments applied. Fluopyram negatively affected the biodiversity indicating greater disturbance for the nematode community structure in the soil. It can be concluded that fluopyram and liquid chicken manure have nematicidal potential, while liquid chicken manure maintained or enhanced nematode biodiversity.